Pemberdayaan Perempuan Dalam Pengembangan Pariwisata Berdasarkan Hukum Adat Tenganan Pegringsingan Dan UNWTO - Mohammad Fadli; Miftahus Sholehudin; Airin Liemanto (Arena Hukum, 2022)
This sociolegal research with an economic and sociocultural approach aims to analyze how the position of Adat Law in Tenganan Pegringsingan Bali with a patrilineal kinship system, places the role of women in overcoming sociocultural impacts, especially in the tourism sector which has fallen due to covid 19. The results show that as a specialized UN agency in the field of tourism, UNWTO is committed to enhancing the positive impact of tourism development on women’s lives, and, in so doing, contributing to the achievement of the Fifth Sustainable Development Goal: “Achieve gender equality and empower all women and girls”. Since 2007, UNWTO has been working, through its Ethics, Culture and Social Responsability Department, in partnership with UN Women and a range of external partners across the globe, to bring gender issues to the forefront of the tourism sector, promoting gender equality and women’s empowerment and encouraging member states to mainstream gender issues in their respective tourism policies.